Consumo de alcohol y benzodiacepinas como afrontamiento del estrés laboral en mujeres - González Ramírez, Patricia (2025)
Introduction: Women are currently entering the workforce with increasing frequency, a situation that entails greater physical and emotional strain due to multiple responsibilities at work and at home. Work-related stress as a response to a double work shift requires the use of coping strategies that can sometimes be related to the use of alcohol and medical drugs. Objective: To examine the use of alcohol and benzodiazepines as coping strategies in women with work-related stress. Materials and Methods: This is a descriptive, cross-sectional study. The population consisted of 440 women over the age of 18 from a higher education institution. Results: Women with higher work stress were found to have higher alcohol and benzodiazepine use as a coping strategy for work-related stress (U = 3814.5, p < .001), with the highest means and medians of work-related stress found in women who consumed alcohol and benzodiazepines (